Prevent falls in older adults - O P Sharma; Raju Vaishya (Apollo Medicine)
Falls are common in the elderly and may lead to serious injuries. Recurrent falls are also frequent and are responsible for significant morbidity and mortality in older adults. The most serious injuries due to these falls are head injury and the fractures. The effect of a fall on an older person can be a devastating event, resulting in chronic pain, loss of independence, and reduced quality of life. Hence, the prevention of fall is better than the treatment of the injuries resulting from it.